(untitled) (Research, Society and Development, 2020)
Describe the vocabulary knowledge of youth son about human immune defense in the presence of Covid 19. Descriptive research, carried out in April 2020, with 64 young high school and university students who participated in the “In Tuning with Health” program on the Radio AJIR website. Knowledge was categorized and analyzed based on the Vocabular Universe and Thematic Analysis. 31 questions-discourses made up the Vocabular Universe of Youths, highlighted for organic and bodily defense, signs and symptoms, forms of transmission, prevention strategies, risk groups, sequelae, immune system, treatment, drugs, vaccine, cure, asymptomatic, social isolation and primary care. Online dialogical communication enabled the exchange of knowledge expressed by experiences in the context of the pandemic in contemporary times. The mediation of youth knowledge about the new coronavirus via web radio was constituted as a practice of educational nursing webcare, motivating health promotion in the context of the pandemic.